Cardiopulmonary factors associated with atrial fibrillation in patients with chronic obstructive pulmonary disease - E. I. Leonova; G. G. Shechyan; V. S. Zadionchenko; T. V. Adasheva; A. D. Deev; I. V. Fedorova (Столичная издательская компания, 2017)
Aim. To study the relationships between clinical and functional features of chronic obstructive pulmonary disease (COPD) and status of cardiovascular system with focus on identifying factors associated with the atrial fibrillation (AF) in patients with COPD.Material and methods. Patients (n=94) with COPD out of exacerbation and airways obstruction of 2-4 degree (GOLD 2013) were examined. The spirometry, daily pulse oximetry, 24-hour ECG and blood pressure monitoring with vascular wall stiffness estimation, echocardiography were performed. Levels of high-sensitivity C-reactive protein (CRP) were also assessed.Results. AF paroxysms were found in 46 patients, including newly diagnosed ones in 22 patients. According to the results of multiple correlation analysis, the frequency of AF paroxysms correlated with forced expiratory volume in 1 sec (FEV1) (R=-0.348; p=0.013), minimum oxygen saturation of the blood (min%SpO2) (R=-0.356; p=0.011), CRP level (R=0.442; p=0.001), the sizes of both atria (p<0.001), isovolumic relaxation time (IVRT) of left ventricle (LV) (R=0.350; p=0.022), the right ventricle (RV) size (R=0.478; p<0.001), systolic blood pressure level in the pulmonary artery (PASP) (р<0.001), vascular stiffness - pulse wave velocity in aorta (PWao) (p=0.001). The influence of FEV1 on the left atrium volume index (χ2=7.0; p=0.008) and IVRT LV (χ2=7.9; p=0.005) was revealed. Correlations between min%SpO2 and IVRT and PWao were observed.Conclusion. Severe bronchial obstruction, hypoxemia, systemic inflammation with increase in vascular stiffness (PWao) and myocardium remodeling (increase in the sizes of both atria, PASP, RV size and diastolic dysfunction of LV) are the factors that associated with the occurrence of AF in patients with COPD.